Accesibilidad universal e inclusión social en la implementación del programa MiBici en Guadalajara, 2014-2019 - Reynoso Delgadillo, Jacob R.; Verduzco Chávez, Basilio (El Colegio de México A.C., 2023)
This article analyzes the implementation trajectory of the MiBici Program in the Metropolitan Area of Guadalajara, Jalisco, in Mexico. It evaluates its contributions to the simultaneous achievement of two goals: The multiplication of accessibility choices using an approach of universal coverage, and the expansion of group affiliation freedoms for persons seeking to build a social identity in the metropolis. Methods used here include census track level statistical analysis of sociodemographic information, analysis of data reported by the program on progress and outcomes of MiBici, as well as information generated by interviews. The key contribution is the use of an analytical model of public policy implementation trajectory with two simultaneous objectives, which allows highlighting progress and setbacks in implementation. Results presented here suggest that the program has made minor contributions on both, but can enhance its performance by using better assessments of supply and demand for mobility options in the metropolitan area, and by introducing changes in public consultation processes.